2020
DOI: 10.1038/s41598-020-57988-7
|View full text |Cite
|
Sign up to set email alerts
|

3D sub-pixel correlation length imaging

Abstract: Quantitative 2D neutron dark-field-imaging with neutron grating interferometry has been used to characterize structures in the size range below the imaging resolution. We present the first 3D quantitative neutron dark-field imaging experiment. We characterize sub-pixel structure sizes below the imaging resolution in tomography by quantitatively analyzing the change in dark-field contrast with varying neutron wavelength. This proof of principle experiment uses a dedicated reference sample with four different so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Up to this point, we have only discussed the simulation of darkfield imaging data in the context of two-dimensional or radiography measurements. However, dark-field imaging can be extended to three-dimensional space via tomography as described by Harti et al (2020). The signal from microstructures contained per voxel will need to be balanced with the overall transmission through our material and the integration over multiple microstructures across the beam path rather than the single structures discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Up to this point, we have only discussed the simulation of darkfield imaging data in the context of two-dimensional or radiography measurements. However, dark-field imaging can be extended to three-dimensional space via tomography as described by Harti et al (2020). The signal from microstructures contained per voxel will need to be balanced with the overall transmission through our material and the integration over multiple microstructures across the beam path rather than the single structures discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that DFI can detect sub-resolution features qualitatively 19,26,40,28,[33][34][35][36][37][38][39] , but until now, methods demonstrating quantification of the size of the unresolved porosity have not been presented in published research. In this research, we present a method to estimate the size of the unresolved pores in a material, based tunable grating interferometry performed at the TOMCAT beamline of the Swiss Light Source (Paul Scherrer Institut).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In dark-field imaging, the ACL is a system parameter of a nTLI that is related to the wavelength of the neutron beam, period of the analyzer grating, and distance between the sample and analyzer grating 9 . Dark-field imaging using a conventional nTLI 13 , 14 has an ACL of several micrometers, meaning it can only analyze sample inhomogeneities in the micrometer range, unlike the conventional range of SANS which is of order nanometers. Therefore, different geometries are required to extend the ACL range to apply dark-field imaging to material studies that have traditionally been conducted using conventional SANS instruments.…”
Section: Introductionmentioning
confidence: 99%